(untitled) (GYMNASIUM, 2009)
A quality service is one which fulfils a set of demands and rules according to a standard and especially according to the internal and external client’s expectations. Reaching these goals implies also a new relationship between the service provider and the beneficiary. As a consequence, in educational system is expected also a change regarding the improvement of the educational offer, the educational context, the quality of the human resources and the relationship between teacher and student. We might know if the educational service we provide is a corresponding one through measurements, statistics and objective data. This allows comparisons and classifications among the educational institutions and they prove the evolution in time also. The progress must be the main criteria for all the decisions, actions and process involved in higher education teaching.